2019
DOI: 10.1021/acscatal.9b01926
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Substrate Activation via an Arginine Residue Drives Catalysis in Chalcone Isomerases

Abstract: Chalcone isomerases are plant enzymes that perform enantioselective oxa-Michael cyclizations of 2¢-hydroxychalcones into flavanones. An X-ray crystal structure of an enzyme-product complex and molecular dynamics simulations reveal an enzyme mechanism wherein the guanidinium ion of a conserved arginine positions the nucleophilic phenoxide and activates the electrophilic enone for cyclization through Brønsted and Lewis acid interactions. The reaction terminates by asymmetric protonation of the carbanion intermed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Therefore, the catalytic efficiency towards 6′-deoxychalcone has been greatly improved. 193 These results provide a theoretical basis for screening novel CHIs and broadening the substrate tolerance of CHIs through mutagenesis.…”
Section: Novel Enzymes and Enzymatic Reactions Leading To Total Synthesis Of Complex Natural Productsmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the catalytic efficiency towards 6′-deoxychalcone has been greatly improved. 193 These results provide a theoretical basis for screening novel CHIs and broadening the substrate tolerance of CHIs through mutagenesis.…”
Section: Novel Enzymes and Enzymatic Reactions Leading To Total Synthesis Of Complex Natural Productsmentioning
confidence: 87%
“… 192 Recently, the reaction mechanisms of enantioselective oxa-Michael cyclisation performed by type I and II CHIs have been revealed by X-ray crystal structure and molecular dynamics simulations, wherein the guanidinium ion of a conserved arginine positions the nucleophilic phenoxide and activates the electrophilic enone for cyclisation through Brønsted and Lewis acid interactions. 193 This mechanism presents a new enantioselective Michael-type reaction in natural product biosynthesis that efficiently constructs C–O bonds. The crystal structure of type II CHI also revealed two unique water molecules in the active pocket which form an ordered hydrogen bond network with the polar amino acids in the pocket.…”
Section: Novel Enzymes and Enzymatic Reactions Leading To Total Synthesis Of Complex Natural Productsmentioning
confidence: 99%
“…5 ), and the dioxygen molecule could occupy the vacancy between C6---Fe and mediate the ignition of the DHP-O 2 -Fe triad. Third, the consequent O-O cleavage could be promoted by neighboring proton donor candidates such as imidazolium of His 105 , neutral form of Asp 320 , aromatic N-H of DHP, and even guanidinium of Arg 293 39 , 40 . Moreover, a crystal structure-based CAVER analysis indicated that the dioxygen tunnels terminate at a position opposite to Ser 302 rather than Asp 320 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen bond network as a defining catalytic motive was documented in various enzymes, for example, chorismate mutase 44 or chalcone isomerase. 45 This concept has also been recognized in small-molecule organocatalysts. 46 Thiourea is a prominent hydrogen-bond donor featuring in a number of organocatalysts, often combined with another activation unit, such as an amine, which provides a powerful tool for a variety of transformations.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Conformational flexibility and defined intramolecular arrangements of peptides offer unique possibilities for catalyst design. Hydrogen bond network as a defining catalytic motive was documented in various enzymes, for example, chorismate mutase or chalcone isomerase . This concept has also been recognized in small-molecule organocatalysts .…”
Section: Introductionmentioning
confidence: 93%